2009
DOI: 10.1007/s10661-008-0705-8
|View full text |Cite
|
Sign up to set email alerts
|

Air quality assessment in Southern Kuwait using diffusive passive samplers

Abstract: Measurements of fortnightly average concentrations of NO, NO2, SO2, H2S, NH3, and volatile organic compounds (VOCs) (aromatics=benzene, toluene, o-xylene, m+p-xylene, ethyl benzene; non-aromatics=nonane and octane) were carried out in the period from 26/10/05 to 24/11/05 at 20 points in the southern part of Kuwait as part of a baseline environmental impact assessment study requested by Kuwait National Petroleum Company. Two waves of triplicate diffusive passive samplers were used. A high volume air sampler was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…The average concentration of NO 2 measured in the first round robin test was not significantly different from that obtained during the second round robin test. These values were relatively higher than those recently measured in El Paso (6-18 ppb), Texas (Sather et al, 2007), Eskişehir of Turkey (11.4 ± 8.6 ppb) (Özden et al, 2008), Mulhouse (11.2 ± 3.2 ppb) of France (de Fouquet et al, 2007) and Az-Zour area (7.89 ppb) of Kuwait (Ramadan, 2010), while they were lower than the occurrence level in Beijing (48.9 ppb) (Meng et al, 2008). NO 2 level in Singapore was very close to the annual mean value (21.4 ppb, converted from 40 µg/m 3 ) of WHO guideline (WHO, 2005).…”
Section: Occurrence Level Of No 2 and Socontrasting
confidence: 54%
“…The average concentration of NO 2 measured in the first round robin test was not significantly different from that obtained during the second round robin test. These values were relatively higher than those recently measured in El Paso (6-18 ppb), Texas (Sather et al, 2007), Eskişehir of Turkey (11.4 ± 8.6 ppb) (Özden et al, 2008), Mulhouse (11.2 ± 3.2 ppb) of France (de Fouquet et al, 2007) and Az-Zour area (7.89 ppb) of Kuwait (Ramadan, 2010), while they were lower than the occurrence level in Beijing (48.9 ppb) (Meng et al, 2008). NO 2 level in Singapore was very close to the annual mean value (21.4 ppb, converted from 40 µg/m 3 ) of WHO guideline (WHO, 2005).…”
Section: Occurrence Level Of No 2 and Socontrasting
confidence: 54%
“…Other sources of primary pollutants in Kuwait include power stations (operating on fossil fuels) and road traffic. A recent study by Ramadan [39] was concerned with measurements of fortnightly average concentrations of a number of primary pollutants, namely: NO, NO 2 , SO 2 , H 2 S, NH 3 , and VOCs. The study location was in southern Kuwait (Al-Zour); an area influenced by petroleum refining and electrical generation activities.…”
Section: Pollutants Monitoring and Major Contributing Sourcesmentioning
confidence: 99%
“…cardiopulmonary diseases, mortality rate and HROQL as previous studies. Second, although Ramadan reported that the NO distribution was similar to that of NO 2 [14], NO 2 /(NO + NO 2 ) in Takamatsu area was positively correlated with years. In general, toxicity of NO 2 is higher than that of NO in plants [6].…”
Section: Discussionmentioning
confidence: 92%